Development of Problem-Based e-LKPDs Assisted by CANVA to Stimulate Numeracy Skill and Visual Literacy - Putri Oktariya; Kartini Herlina; Abdurrahman Abdurrahman (Postgraduate, University of Mataram, 2023)
This research aims to determine the validity of e-LKPD. As well as stimulating students' visual literacy and numeracy skills through the development of problem-based e-LKPD. The population in this study were students of class XII MIA at SMAN 1 Abung Selatan, North Lampung Regency for the 2023/2024 academic year. This research is a Design and Development Research (DDR) empirical research with 4 procedures or stages, namely, analysis, design, development. With a pretest posttest control group design. Data collection was carried out using test and observation methods. Problem-based learning is applied in the experimental class while Direct Instructor (DI) is the Control class. The results of the research showed that the experimental class students' numeracy and visual literacy skills increased by 0.71, while the control class increased by 0.56. Based on the results of this research, it shows that the problem-based e-LKPD experienced an increase in both the experimental class's numeracy and visual numeracy skills. compared to the control class. The results of the t-test show that it has a positive influence on students' visual literacy and numeracy skills with output results (49) = 0.235. So it can be concluded that the application of problem-based e-LKPD can improve students' visual literacy and numeracy skills.